Let be \( f : x \longmapsto f(x) \) a function of class \( \mathcal{C}^n \) and \( f^{(n)} \) its \( n \)-th derivative.
The Taylor-Young's formula tells us that any function \( f_{n,a} \), centered at \( x = a \), can be written as a Taylor series \( (TS_n(a)) \) with a remainder \(R_n\), such as:
Here is the decomposed form:
So,
Furthermore, setting down \( (x = a + h) \), we do obtain a new form of this formula:
So,
Recap of the main Taylor series
Starting from the main equation of the fundamental theorem of calculus:
So,
Performing an integration by parts, with a wise choice for \( u \) and \( v' \), we do have:
$$ \Biggl \{ \begin{gather*} u(t) = f'(t) \\ v'(t) = -dt \end{gather*} $$
Then we do it again with:
And so on...
Thus, the function\( f \) accept a Taylor series with integral remainder \( R_{n,a}(x) \) and this function is worth:
So,
Furthermore, setting down \( (x = a + h) \), we do obtain a new form of this formula:
So,
Another notation used to characterize the remainder of an Taylor series is the Landau notation \(o(x^n)\).
If a function \( f(x) \) is negligible compared to another function \( g(x) \) near a certain point \( a \), we can write it as:
It means that:
In our specific case, we study Taylor series at the neighbourhood of \(( a = 0 ) \), so:
$$ condition $$
|
$$ function $$
|
$$ Taylor \ series \ at \ 0 \ : T_n(0) $$
|
$$ \equiv T_n(0) $$
|
---|---|---|---|
$$ \forall x \in \mathbb{R}, \ \forall \alpha \in \hspace{0.05em} \mathbb{N}^*, $$
|
$$ (1+x)^{\alpha}$$
$$ (Newton's \ binomial) $$
|
$$ 1 + \alpha x + \binom{\alpha}{2}x^2 + \binom{\alpha}{3}x^3 \ ... \ + \binom{\alpha}{\alpha}x^{\alpha} + o(x^{\alpha})$$
|
$$ \sum_{p = 0}^{\alpha} \binom{\alpha}{p} x^k + o(x^{\alpha}) $$
|
$$ \forall x \in \Bigl[ \mathbb{R} \hspace{0.2em} \backslash \bigl\{ -1 \bigr\} \Bigr], $$
|
$$ \frac{1}{1+x}$$
|
$$ 1 - x + x^2 - x^3 + \ ... \ + (-1)^n x^n + o(x^n)$$
|
$$ \sum_{k=0}^n (-1)^k x^k + o(x^n) $$
|
$$ \forall x \in \Bigl[ \mathbb{R} \hspace{0.2em} \backslash \bigl\{ 1 \bigr\} \Bigr], $$
|
$$ \frac{1}{1-x}$$
|
$$ 1 + x + x^2 + x^3 + \ ... \ + x^n + o(x^n)$$
|
$$ \sum_{k=0}^n x^k + o(x^n) $$
|
$$ \forall x \in [-1, \hspace{0.1em} + \infty[, $$
|
$$ \sqrt{1+x}$$
|
$$ 1 + \frac{1}{2}x - \frac{1}{8}x^2 + \frac{1}{4}x^3 - \frac{15}{16}x^4 \ ... \ + o(x^{4})$$
|
$$ $$
|
$$ \forall x \in \hspace{0.05em} ]-1, \hspace{0.1em} + \infty[, $$
|
$$ 1 \over \sqrt{1+x}$$
|
$$ 1 - \frac{1}{2}x + \frac{3}{4}x^2 - \frac{15}{8}x^3 + \frac{105}{16}x^4 \ ... \ + o(x^{4})$$
|
$$ $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ e^x $$
|
$$ 1 + x + \frac{x^2}{2!} + \frac{x^3}{3!} + \ ... \ + \frac{x^n}{n!} + o(x^n)$$
|
$$ \sum_{k=0}^n \frac{x^k}{k!} + o(x^n) $$
|
$$ \forall x \in \hspace{0.05em} ]-1, \hspace{0.1em} + \infty[, $$
|
$$ ln(1+x) $$
|
$$ x - \frac{x^2}{2} + \frac{x^3}{3} - \frac{x^4}{4} + \ ... \ + \frac{ (-1)^{n-1} }{n} x^n + o(x^{n})$$
|
$$ \sum_{k=1}^n \frac{ (-1)^{k-1} }{k} x^k + o(x^{n}) $$
|
$$ \forall x \in \hspace{0.05em} ]1, \hspace{0.1em} + \infty[, $$
|
$$ ln(1-x) $$
|
$$ -x - \frac{x^2}{2} - \frac{x^3}{3} - \frac{x^4}{4} - \ ... \ - \frac{x^n}{n} + o(x^{n})$$
|
$$ \sum_{k=1}^n -\frac{ x^k }{k} + o(x^{n}) $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ sin(x) $$
|
$$ x - \frac{x^3}{3!} + \frac{x^5}{5!} - \frac{x^7}{7!} \ ... \ + (-1)^n \frac{x^{2n+1}}{(2n+1)!} + o(x^{2n+2})$$
|
$$ \sum_{k=0}^n (-1)^k \frac{x^{2k+1}}{(2k+1)!}+ o(x^{2n+2}) $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ cos(x) $$
|
$$ 1 - \frac{x^2}{2!} + \frac{x^4}{4!} - \frac{x^6}{6!} + \ ... \ + (-1)^{n} \frac{x^{2n}}{(2n)!} + o(x^{2n+1})$$
|
$$ \sum_{k=0}^n (-1)^{k} \frac{x^{2k}}{(2k)!} + o(x^{2n+1}) $$
|
$$\forall k \in \mathbb{Z}, \enspace \forall x \in \biggl[ \mathbb{R} \hspace{0.2em} \backslash \Bigl\{ \frac{\pi}{2} + k\pi \Bigr\} \biggr],$$
|
$$ tan(x) $$
|
$$ x + \frac{1}{3}x^3 + \frac{2}{15}x^4 + \frac{17}{315}x^6 + \ ... \ + o(x^{6})$$
|
$$ $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ arctan(x) $$
|
$$ x - \frac{x^3}{3} + \frac{x^5}{5} - \frac{x^7}{7} \ ... \ + (-1)^n \frac{x^{2n+1}}{(2n+1)} + o(x^{2n+2})$$
|
$$ \sum_{k=0}^n (-1)^k \frac{x^{2k+1}}{(2k+1)}+ o(x^{2n+2}) $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ sinh(x) $$
|
$$ x + \frac{x^3}{3!} + \frac{x^5}{5!} + \frac{x^7}{7!} \ ... \ + \frac{x^{2n+1}}{(2n+1)!} + o(x^{2n+2})$$
|
$$ \sum_{k=0}^n \frac{x^{2k+1}}{(2k+1)!}+ o(x^{2n+2}) $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ cosh(x) $$
|
$$ 1 + \frac{x^2}{2!} + \frac{x^4}{4!} + \frac{x^6}{6!} + \ ... \ + \frac{x^{2n}}{(2n)!} + o(x^{2n+1})$$
|
$$ \sum_{k=0}^n \frac{x^{2k}}{(2k)!} + o(x^{2n+1}) $$
|
$$ \forall x \in \mathbb{R}, $$
|
$$ tanh(x) $$
|
$$ 1 + \frac{x^2}{2!} + \frac{x^4}{4!} + \frac{x^6}{6!} + \ ... \ + \frac{x^{2n}}{(2n)!} + o(x^{2n+1})$$
|
$$ \sum_{k=0}^n \frac{x^{2k}}{(2k)!} + o(x^{2n+1}) $$
|
$$ \forall x \in \hspace{0.05em} ]-1, \hspace{0.1em} 1[, $$
|
$$ tanh(x) $$
|
$$ x - \frac{1}{3}x^3 + \frac{2}{15}x^4 - \frac{17}{315}x^6 + \ ... \ + o(x^{6})$$
|
$$ $$
|
$$\forall k \in \mathbb{Z}, \enspace \forall x \in \biggl[ \mathbb{R} \hspace{0.2em} \backslash \Bigl\{ \frac{\pi}{2} + k\pi \Bigr\} \biggr], $$
|
$$ csc\left(\frac{\pi}{2} + x \right) = sec(x) $$
|
$$ 1 + \frac{x^2}{2!} + \frac{x^4}{4!} + 61 \frac{x^6}{6!} + \ ... \ + o(x^{6})$$
|
$$ $$
|
$$\forall k \in \mathbb{Z}, \enspace \forall x \in \biggl[ \mathbb{R} \hspace{0.2em} \backslash \Bigl\{ \frac{\pi}{2} + k\pi \Bigr\} \biggr], $$
|
$$ cot\left(\frac{\pi}{2} + x \right) = -tan(x)$$
|
$$ -x -\frac{1}{3}x^3 -\frac{2}{15}x^4 -\frac{17}{315}x^6 + \ ... \ + o(x^{6})$$
|
$$ $$
|
Let us use the previously demonstrated method to calculate a Taylor series of the \( sin(x) \) function.
We firstly verify that \( sin(x) \) can be derivated three times in a row. It is well-known that is the case.
Then, let us calculate the successive derivatives of order \(3 \), and retrieve all of these images at \( a = 0 \).
Now, we apply the Taylor-Young's formula.
In our case, that would be:
We have seen above that this remainder is worth:
But, \(sin^{(4)}(t) = sin(t)\). So we now have a new expression for \( R_{3, 0}(x)\):
Let us now frame this remainder in the interval \( [-\pi, \pi]\).
Using the property of growth of an integral, we do have:
Yet, we know thanks to \((1)\) that:
This leads us to a framing for \( sin_{3, 0}(x)\) :
Performing an Taylor series of order \(n\) at \((x=0)\) for the \(sin(x)\) function, we obtain:
Moreover, the remainder of this Taylor series is worth:
With the Taylor-Lagrange's inequality, we can frame this remainder:
$$ \Bigl|R_{n, 0}(x) \Bigr| \leqslant M \Biggl | \frac{x^{2n+2}}{(2n+2)!} \Biggr|$$ $$ with \enspace M = max \Bigl\{cos(0) ; \hspace{0.2em}cos(x) \Bigr\} = 1 $$
By compared growth of the limits, the factorial function outweighs the power of x function:
In the end, with the squeeze theorem:
So as a result, a Taylor series of the \(sin(x) \) function is worth: